2016
DOI: 10.5194/pb-3-23-2016
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and monitoring behaviors by leaders predict following in wild Barbary macaques (<i>Macaca sylvanus</i>)

Abstract: Abstract. For group-living animals it is essential to maintain the cohesiveness of the group when traveling. Individuals have to make an accurate decision about where and when to move. Communication before and during the departure of the first individual may play a crucial role in synchronizing a collective movement. We hypothesized that individuals in a wild primate group use signals or cues prior to and after departure to achieve collective movements. With two observers we used all-occurrences behavior sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Social centrality significantly affected the frequency of visual signals. The study by Seltmann et al demonstrated a negative correlation between the strength of social connections and the frequency of back-glance in Barbary macaques [ 9 ]. However, in a previous study related to group movements in Tibetan macaques, we found a positive correlation between the strength of social connections and the frequency of successful initiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Social centrality significantly affected the frequency of visual signals. The study by Seltmann et al demonstrated a negative correlation between the strength of social connections and the frequency of back-glance in Barbary macaques [ 9 ]. However, in a previous study related to group movements in Tibetan macaques, we found a positive correlation between the strength of social connections and the frequency of successful initiation.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this is because the pause signal usually occurs when foraging is over, during the group departs from the feeding site into the forest and lasts long. Back-glance is not needed to monitor or recruit when a certain number of participants are present [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In primate species, initiation of a group movements can be accompanied by notifying behaviors (Kummer 1968) or preliminary behaviors (Sueur and Petit 2008a) that are exhibited in the pre-departure period, directly preceeding the group movement. This recruitment process often includes visual and acoustic communication, and which can influence the recruitment success of an initiation, i.e., whether the initiator is followed and, if so, by how many group members and how quickly Seltmann et al 2016;Sperber et al 2017).…”
mentioning
confidence: 99%